INSTILLING STUDENT DISCIPLINE THROUGH THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS - Malik, Muhammad; Sunardi (Tsaqofah : Jurnal Pendidikan Islam, 2022)
Discipline is a very important thing to get used to in every line of human life, because discipline is an exercise of memory and character to create self-control. Teachers have very complex roles and tasks, ranging from motivating and being a role model for students so that the potential that exists in students can develop and increase. The approach used in this study is a qualitative approach. Researchers chose SDIT Kuntum Insan Cemerlang Bondowoso as a place of research using observation, interviews and documentation. The results showed that instilling student discipline through the role of Islamic religious education teachers as role models and motivators was very large. This is evidenced by the changes and improvements in student discipline that are very good. The increase in student discipline certainly cannot be separated from the role of Islamic religious education teachers who always provide examples and motivation to students, so that students become more disciplined in following lessons in an orderly manner and obeying the rules in school. Researchers also found a new finding at SDIT Kuntum Insan Cemerlang Bondowoso, namely, the teacher arrived earlier than the students.